Post-Disaster Engineering Strategy for Anai River Debris Flow Management on Anai Valley National Road West Sumatra Indonesia - Andriani Andriani; Bambang Istijono; Rahmad Yuhendra; Mahdi Mahdi; Muhammad Al Giffari; Arian Dodi; Bayu Martanto Adji (Journal of Applied Engineering and Technological Science (JAETS), 2024)
One of the causes of flash floods is eruption material from Mount Marapi that is carried downstream, disrupting transportation access and the local economy. This study aimed to design and implement an effective post-disaster engineering strategy for debris flow management in the Anai River and evaluate its long-term success. Data were collected through field observations to measure river profiles, photogrammetry, and sediment sampling. Secondary data were used to calculate rainfall intensity and flood discharge in the Anai River to plan debris flow control. The study results showed that the large catchment area and high rainfall contributed significantly to the high peak discharge. Disturbed soil samples taken from the river surface were saturated, indicating the influence of sediment from the debris flow from the eruption of Mount Marapi. The removal of material from the riverbed needs to be controlled to avoid overexploitation that could exacerbate erosion of the riverbanks, ultimately threatening bridge structures and other infrastructure along the Anai River. To overcome this problem, it is necessary to build sediment control structures such as check dams and groundsills, as well as secure riverbanks in the management of debris flows in the Anai River.